Current Status of Supplementary English Programs in East Java Indonesia - Yusuf , Achmad; Rachmawati, Amalia; Munir, Ahmad (New Language Dimensions, 2023)
This study aimed to investigate the position of supplementary English programs in senior high schools in Indonesia and the use of literature and linguistics in the program. This research employed a mixed method using a survey with a semi-structured questionnaire. Twenty-seven English teachers of senior high schools in East Java were invited through the social media WhatsApp Group to fill in the Google Form. It was found that not many supplementary English programs are run in senior high schools in East Java. The small number of students in the language programs also shows that few students choose supplementary English programs over other programs. Moreover, teachers employed various literature genres, linguistics, and sociolinguistics during classroom activities. The teachers of supplementary English programs in Indonesia also introduced students to intercultural communicative competence. It can be concluded that even though the supplementary English programs in senior high schools in East Java are small in number, their implementation is thriving and promising for ELT in the future.